Some questions regarding the new regulations of crimes against "sexual inviolability and sexual freedom" by the new Criminal Code of the Republic of Armenia - Simonyan, Tigran (Bulletin of Yerevan University C: Jurisprudence, 2023)
The article is devoted to the study of a number of controversial issues related to the legal regulation of crimes against "Sexual freedom and sexual inviolability" provided by the new Criminal Code of the Republic of Armenia. Within the framework of the article, based on a comparative analysis, many problems have been identified that can negatively affect the process of qualifying crimes, disrupting the normal course of law enforcement activities. Within the framework of the article, a number of recommendations for changing the legislation are given. In particular, it was noted that the crimes of rape and sexual assault are united by the new legislation, but the risk of rape is higher than other sexual assault and the question of its separate includance remains open.It is stated that it is more than strange to single out “imitation of sexual intercourse” as a form of the sexual assault. Imitation of sexual intercourse is most common for children when they try to imitate sexual relations of their parents or other adults. Reference was also made to the unfortunate wording of aggravating circumstances, whereby a person who has not reached the age of 12 within the meaning of the article under discussion is no longer considered to be in a helpless state.The problematic elements of the wording "without the reasonable consent of the victim" are discussed. It has been recorded that the artificial introduction of conventional norms into our criminal legislation, as well as crimes provided for by the criminal legislation of foreign states, without their localization and without taking into account the peculiarities of national legislation, can have very negative consequences.
Keywords: crimes against sexual freedom and inviolability; he new Criminal Code of the Republic of Armenia; rape and sexual violence; imitation of a sexual intercourse or satisfaction of a sexual need; sexual penetration; a person under 12 years of age,; consent to sexual activity; child pornography; grooming